High parity and hormonal contraception use as risk factors for cervical cancer in East Kalimantan (Faculty of Medicine Universitas Indonesia, 2010)
Aim: To find risk factors associated with cervical cancer. Methods: This a case-control study conducted in A.W. Sjahranie County General Hospital at Samarinda East Kalimantan from January until July 2009. There were 58 patients for each case and control group. Variables in this study were age, menarche, menopause, age of first marriage, parity, spouse's smoking status, hormonal contraception use, type of hormonal contraception, duration of hormonal contraception, IUD (intra uterine device) contraception use and duration of IUD contraception. Results: final data analysis shows that parity and duration of hormonal contraception use increased the risk of cervical cancer. Women who had 5-12 children than 0-4 children had 2.6-folds increased risk to be cervical cancer. Compared to women never use of hormonal contraception, those who ever had hormonal contraception for 1-4 years and 5-25 years had two time and 4.5 times increased risk to be cervical cancer respectively. Conclusion: Cervical cancer screening recommended to be focused on high-risk groups, among others, women with the number of children born more than five people or women in particular users of hormonal contraception methods with a range of use more than five years. (Med J Indones 2010; 19:268-72)